“Nothing is created…”: crossfit as a resignified body practice - Fortunato, Jonatan (2019)
The purpose of this paper is to carry out an analysis comparing Crossfit to body practices systematized before its appearance. We aimed at verifying if such practices had any connection to what Crossfit has become. We begin by introducing Crossfit, evidencing its main aspects, as well as exploring its origins. We dialogue with academic literature as well as information gathered from official sources of this modality. In conclusion, we notice that Crossfit arise as a way to institutionalize previous practices, derived especially from German Gymnastics and Calisthenics. In this way, the modality appropriates practices that are already known, resignify them and use them as a means to develop the “complete” athlete.